Independent and synergistic impact of mouth rinsing with L-menthol, carbohydrate, caffeine, and combination L-menthol + carbohydrate + caffeine on intermittent performance in recreationally active young men / Muhammad Azizi Shah ... [et al.]. - Shah, Muhammad Azizi; Linoby, Adam; Farhani, Nur Irdina; Mohd Dan, Azwa Suraya; Kamaruddin, Harris Kamal; Nugraha, Reshandi; Machado, Marco (2024)
This study examined the hypothesis that mouth rinsing with carbohydrate (CHO), caffeine (CAF), L-menthol (MEN), and their combination (CHO+CAF+MEN; MIX) would improve performance during high-intensity intermittent exercise. Eighteen recreationally active young men (mean ± SD: age 22 ± 2 years, body mass 62 ± 7 kg, height 168 ± 0.06 cm) participated in a randomized, double-blind, placebo-controlled crossover study. Participants completed six trials involving mouth rinsing with CHO, CAF, MEN, MIX, a placebo (PLA), and a control (CON; plain water). The CHO mouth rinse (1440 ± 288 m) significantly enhanced exercise performance in the Yo-Yo intermittent recovery level 1 (Yo-Yo IR1) test compared to PLA (1383 ± 282 m) and CON (1373 ± 282 m) (both p < 0.05), but not when compared to other rinses. There were no significant differences in heart rate (HR), muscle oxygenation (SmO2), blood lactate, or blood glucose levels between the different mouth rinse conditions. These results suggest that CHO mouth rinsing can improve intermittent exercise performance without affecting physiological markers such as HR, SmO2, lactate, or glucose. Further research should explore the mechanisms behind these performance improvement effects and the potential benefits for different athletic populations.